MAD2L2 dimerization and TRIP13 control shieldin activity in DNA repair - Inge de Krijger (Nature Portfolio, 2021)
MAD2L2 — a member of the shieldin complex — is known to play important roles in DNA repair. Here the authors demonstrate how MAD2L2 dimerization mediated through SHLD2 participates in shieldin assembly and function.